The Corellation of Hypnoanasthesia with Pain Degree on Installation of Intra Uterine Device (IUD) - Rahayu, Indah (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims : this study was to analyze the difference of median pain of IUD insertion in hypnoanasthesia group and IUD mounting standard group, to analyze the difference of pain reduction scores of IUD insinuation on hypnoanasthesia group and IUD mounting standard group and to analyze hypnoanasthesia relationship with degree of pain in the installation of Intrauterine Device (IUD). Research : research design used quasi experimental approach with two group post test only with control group design. Analysis of results using Mann-Whitney and Chi-Square test. Results : result of the research shows that there is difference of pain score of hypnoanasthesia group that is median value 4 and standard group of IUD insertion with median value 5 and obtained p value <0.001. There was a difference of pain reduction score in the hypnoanasthesia group of 60% and in the standard group of 33.3% with p = 0.002. There is a correlation of hypnoanasthesia with degree of pain in IUD insertion with p value = 0.005. Conclusions : the hypnosis method emphasizes the emergence of positive suggestion, calm feeling, and relaxation that make it comfortable. When the condition is calm and relaxed, the brain will automatically release the hormone endorphins that reduce pain and give a sense of comfort and relaxation.